Test in sorghum lines in the semi-arid region of pernambuco for human consumption - Tabosa, José Nildo; de França, Geraldo Eugênio; Santos, José Peroba Oliveira; Maciel, Grabiel Alvez; Lira, Mário de Andrade; de Araújo, Marcelo Renato Alvez; Guerra, Nonete Barbosa (Pesquisa Agropecuaria Brasileira, 1993)
The objective of this work was to evaluate grain sorghum cultivars to the Semi-Arid region of the state of Pernambuco and utilization possibility of this cereal for human consumption. The works were carried out in three localities of the Semi-Arid region in 1985 and 1986. Twelve grain sorghum cultivars were evaluated in field conditions by: blooming, plant height, panicle number and grain yield. The experimental design was a randomized block. In laboratory conditions the parameters utilized were: color, protein, tannin and flour efficiency in the grain. The sorghum cultivars IPA-8602489, IPA-8602517, IPA-8602473 and IPA-8602484 showed grain production average above 5,0 t/ha. Besides, most of these cultivars showed grain colors varying from white to pearl-yellow. The flour efficiency presented was of 70 to 90 percent, with low tannin.